Analisis Pelayanan Home Visite Orang Dengan Gangguan Jiwa Di RSJ Kalawa Atei Provinsi Kalimantan Tengah - Muhammad Rustam Effendy; Raden Biroum Bernardianto; Putri Irianti Sintaman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This study aims to analyze the home visite services of people with mental disorders in Kalawa Atei General Hospital in Central Kalimantan Province. Given the implementation of the program for people with mental disorders to access health services whose handling is different from other health services. This study uses a qualitative approach that aims to describe the complexity and dynamics of handling people with mental disorders. The primary data in this study were sourced from several informants, namely Home Visite Officers from Kalawa Atei General Hospital, Social Service and Povinsi / Regency Health Service, local Puskesmas, and Family of Ganguan Mental Panderita. Meanwhile, Secondary Sources in this study include the Implementation of Home Visite Regulation, Home Visite Service Profile, Home Visite Patient Ratio and other related documents. The results of the study show the conclusions of the study that the implementation of home visite services organized by the Central Kalimantan Atei Central Hospital along with other cross sectors has been running quite well. This is seen in terms of the facilities and infrastructure that have been provided in providing home visite services for ODGJs that have been prepared and are maximally sought. Home visite services are in accordance with SOPs, competencies and disciplines of each service officer. Home visite services provide guarantees to each patient with a special schedule by officers to come to the regions to provide these services. In this case, home visite services in terms of empathy by service personnel are good enough. Considering that home viste activities are shown to severely mentally ill patients, who cannot access Kalawa Atei General Hospital for various reasons, such as financial incapacity, no family support, family ignorance, and the existence of savings. However, there are several inhibiting factors in the implementation of the Home Visite Service at Atawa Kalawa Hospital, namely: 1) equipment completeness, 2) field conditions, 3) communication.